High-flow propylene-based copolymer composition

KR103019717B1Active Publication Date: 2026-09-16DOW GLOBAL TECHNOLOGIES LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227041719
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-29
Filing Date
2021-04-29
Publication Date
2026-09-16
Estimated Expiration
2041-04-29

Smart Images

  • Figure 112022127134264-PCT00001
    Figure 112022127134264-PCT00001
  • Figure 112022127134264-PCT00002
    Figure 112022127134264-PCT00002
  • Figure 112022127134264-PCT00005
    Figure 112022127134264-PCT00005
Patent Text Reader

Abstract

As a composition, the following components: a) at least one propylene / ethylene copolymer or at least one propylene / alpha-olefin copolymer, each comprising the following characteristics: i) Melting point Tm of 60℃ to 85℃, ii) Viscosity of 3,000 cP to 30,000 cP (177℃); b) at least one wax; c) comprising at least one oil; A composition having a weight ratio of component b to component c of 0.30 to 4.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] Cross-reference of related applications

[0002] This application claims priority to U.S. Provisional Application No. 63 / 017541 filed on April 29, 2020, the full text of which is incorporated herein by reference. Background Technology

[0003] Modular carpet tile manufacturers are seeking recyclable and low-viscosity alternatives to bitumen for use as carpet backings. These alternatives must meet market processing and performance requirements. Ethylene / octene random copolymers and block copolymers with low melt flow (melt index approx. 30 g / 10 min, 2.16 kg at 190°C) are currently used in commercial hot melt adhesive (HMA) carpet backing products. While HMA formulations containing polymers, tackifiers, waxes, and oils meet the performance requirements of modular carpet tiles, current formulations are 5 to 10 times more viscous than conventional bitumen formulations. Consequently, current HMA formulations are limited in marketability because they require processing with specialized equipment.

[0004] Adhesives intended for use as modular carpet backings must have low viscosity (less than 30,000 cP at 165°C for unfilled formulations), excellent dimensional stability (expressed in Young's modulus), and a high tensile strain at break. Additionally, the assembled modular carpet tiles must be able to bend completely on their own without cracking (excellent flexibility, expressed as a high tensile strain at break).

[0005] U.S. Patent No. 7,700,707 discloses an adhesive comprising a functionalizing component and an olefin polymer. The olefin polymer comprises at least 50 weight percent of C3-C30 alpha-olefins and at least 50 ppm of dienes. The polymer has a weight-average molecular weight (Mw) of 10,000 to 100,000 g / mol in part and a heat of fusion of 1 to 70 J / g. Refer to Claim 1. The polymer is combined with tackifiers, waxes, and / or oils and used in adhesive formulations. Refer to U.S. Patent No. 7,524,910. U.S. Patent No. 7,294,681 discloses a branched olefin polymer having an Mw of 10,000 to 100,000 g / mol in part, amorphous segments, and semicrystalline segments. Refer to Claim 1. Polymers are combined with tackifiers, waxes, and / or oils and used in adhesive formulations.

[0006] U.S. Publication No. 2016 / 0102429 discloses a carpet backing composition comprising a first polymer component comprising a filler, a compatibilizer, and an elastomeric polymer. The compatibilizer provides a source of free radicals that bind the first polymer component and the filler. Refer to Claim 1. Additional polymers and compositions for applications that may include a carpet component are disclosed in the following references: U.S. Patent No. 9051683, U.S. Patent No. 9365711, U.S. Patent No. 7357971, U.S. Publication No. 2011 / 0256335, International Publication WO 2016 / 029006, and International Publication WO 2009 / 086091.

[0007] However, adhesive compositions in the industry do not provide low-viscosity polymer compositions (fillers) with the required mechanical properties useful for backings for modular carpet tiles. Therefore, for good processability on standard manufacturing lines, there is a need for adhesive compositions with low viscosity and improved performance (e.g., optimal modulus and high tensile strain at break) in carpet backing formulations. Preferably, such compositions are recyclable. These requirements are met by the following invention.

[0008] As a composition, the following ingredient :

[0009] a) A copolymer comprising at least one propylene / ethylene copolymer or at least one propylene / alpha-olefin copolymer, each having the following characteristics:

[0010] i) Melting point Tm of 60℃ to 85℃,

[0011] ii) Viscosity of 3,000 cP to 30,000 cP (177℃);

[0012] b) At least one wax;

[0013] c) Includes at least one oil;

[0014] Component b for Component c A composition having a weight ratio of 0.30 to 4.0. Specific details for implementing the invention

[0015] A composition has been discovered that has improved mechanical properties (Young's modulus, tensile strain at break) and an overall lower viscosity (165°C). This composition is highly suitable as a carpet backing material, particularly for modular carpet tiles.

[0016] As discussed above, the following ingredient A composition comprising:

[0017] a)A copolymer comprising at least one propylene / ethylene copolymer or at least one propylene / alpha-olefin copolymer, each having the following characteristics:

[0018] i) Melting point Tm (DSC) of 60°C to 85°C,

[0019] ii) Viscosity of 3,000 cP to 30,000 cP (177℃);

[0020] b) At least one wax;

[0021] c) Includes at least one oil;

[0022] Component b for Component c A composition having a weight ratio of 0.30 to 4.0.

[0023] The composition of the present invention may include one or more embodiments described herein. Each Components (a, b, c) It may include one or more embodiments as described.

[0024] In one embodiment or a combination of two or more embodiments, each as described herein Component a It has Tm ≥ 62°C, or ≥ 63°C, or ≥ 64°C, or ≥ 65°C, or ≥ 66°C, or ≥ 67°C, or ≥ 68°C. Tm is determined by DSC as described in the "Test Methods" section. In one embodiment or a combination of two or more embodiments, each as described herein Component a Tm ≤ 84℃, or ≤ 83℃, or ≤ 82℃, or ≤ 81℃, or ≤ 80℃, or ≤ 79℃, or ≤ 78℃, or ≤ 77℃, or ≤ 76℃.

[0025] In one embodiment or a combination of two or more embodiments, each as described herein Component aIt has a viscosity (177°C) ≥ 3,500 cP, or ≥ 4,000 cP, or ≥ 4,200 cP, or ≥ 4,400 cP, or ≥ 4,600 cP, or ≥ 4,800 cP, or ≥ 5,000 cP, or ≥ 5,200 cP, or ≥ 5,400 cP, or ≥ 5,600 cP, or ≥ 5,800 cP, or ≥ 6,000 cP, or ≥ 6,200 cP, or ≥ 6,400 cP, or ≥ 6,600 cP, or ≥ 6,800 cP, or ≥ 7,000 cP, or ≥ 7,200 cP. In one embodiment or a combination of two or more embodiments, each described herein Component a It has a viscosity (177℃) ≤ 28,000 cP, or ≤ 26,000 cP, or ≤ 24,000 cP, or ≤ 22,000 cP, or ≤ 20,000 cP, or ≤ 18,000 cP, or ≤ 16,000 cP, or ≤ 15,000 cP, or ≤ 14,000 cP, or ≤ 13,000 cP, or ≤ 12,000 cP, or ≤ 11,000 cP, or ≤ 10,000 cP.

[0026] In one embodiment or a combination of two or more embodiments, the composition described herein is Component b for Component c The weight ratio of is ≥ 0.35, or ≥ 0.40, or ≥ 0.45, or ≥ 0.50, or ≥ 0.52, or ≥ 0.54, or ≥ 0.56, or ≥ 0.58, or ≥ 0.60, or ≥ 0.62. In one embodiment or a combination of two or more embodiments, the composition described herein is Component b for Component c The weight ratio of is ≤ 3.9, or ≤ 3.8, or ≤ 3.7, or ≤ 3.6, or ≤ 3.5, or ≤ 3.4, or ≤ 3.3, or ≤ 3.2, or ≤ 3.0, or ≤ 2.8, or ≤ 2.6, or ≤ 2.4, or ≤ 2.2, or ≤ 2.0, or ≤ 1.8, or ≤ 1.6.

[0027] In one embodiment or a combination of two or more embodiments, each described herein Component a The density is ≥ 0.860 g / cc, or ≥ 0.861 g / cc, or ≥ 0.862 g / cc, or ≥ 0.863 g / cc, or ≥ 0.864 g / cc, or ≥ 0.865 g / cc, or ≥ 0.866 g / cc, or ≥ 0.867 g / cc, or ≥ 0.868 g / cc (1 cc = 1 cm³). In one embodiment or a combination of two or more embodiments, each as described herein Component a The density is ≤ 0.874 g / cc, or ≤ 0.873 g / cc, or ≤ 0.872 g / cc, or ≤ 0.871 g / cc, or ≤ 0.870 g / cc.

[0028] In one embodiment or a combination of two or more embodiments, each as described herein Component a is a propylene / ethylene copolymer, additionally a propylene / ethylene copolymer.

[0029] In one embodiment or a combination of two or more embodiments, each as described herein Component a The density / Tm ratio is ≥ 0.008, or ≥ 0.009, or ≥ 0.010, or ≥ 0.011 (g / (cc·℃)). In one embodiment or a combination of two or more embodiments, each as described herein Component a The density / Tm ratio is ≤ 0.020, or ≤ 0.019, or ≤ 0.017, or ≤ 0.016, or ≤ 0.015, or ≤ 0.014 (g / (cc·℃)).

[0030] In each of the embodiments described herein or a combination of two or more embodiments, the composition Ingredient d) : Includes at least one additional filler.

[0031] In one embodiment or a combination of two or more embodiments, the composition described herein is Component d for component aThe weight ratio of is ≥ 5.00, or ≥ 6.00, or ≥ 7.00, or ≥ 8.00. In one embodiment or a combination of two or more embodiments, each of the compositions described herein is Component d for component a The weight ratio of is ≤ 15.0, or ≤ 14.0, or ≤ 13.0, or ≤ 12.0, or ≤ 11.0, or ≤ 10.0.

[0032] In each of the embodiments described herein or a combination of two or more embodiments, the composition is Ingredient e) Further comprises: an anhydride functionalized and / or carboxylic acid functionalized olefinic polymer, further comprising an anhydride-grafted and / or carboxylic acid-grafted olefinic polymer. In one embodiment or a combination of two or more embodiments, each as described herein Ingredient e is an anhydride functionalized and / or carboxylic acid functionalized propylene-based polymer, and additionally an anhydride grafted and / or carboxylic acid grafted propylene-based polymer.

[0033] In one embodiment or a combination of two or more embodiments, the composition described herein is Component a for component e The weight ratio of is ≥ 15, or ≥ 16, or ≥ 17, or ≥ 18, or ≥ 19, or ≥ 20.

[0034] In each of the embodiments described herein or a combination of two or more embodiments, the composition Component a for component e The weight ratio of is ≤ 30, or ≤ 28, or ≤ 26, or ≤ 25, or ≤ 24, or ≤ 23, or ≤ 22.

[0035] In one embodiment or a combination of two or more embodiments, the composition described herein is component f) : additionally includes at least one tackifier.

[0036] In one embodiment or a combination of two or more embodiments, each as described herein Ingredient dA composition having has a viscosity (165°C) ≥ 10,000 cP, or ≥ 12,000 cP, or ≥ 14,000 cP, or ≥ 16,000 cP, or ≥ 18,000 cP, or ≥ 20,000 cP. In one embodiment or a combination of two or more embodiments, each as described herein Ingredient d A composition having a viscosity (165°C) ≤ 50,000 cP, or ≤ 48,000 cP, or ≤ 46,000 cP, or ≤ 44,000 cP, or ≤ 42,000 cP, or ≤ 40,000 cP, or ≤ 38,000 cP, or ≤ 36,000 cP, or ≤ 34,000 cP.

[0037] In one embodiment or a combination of two or more embodiments, each of the compositions described herein has a tensile strain at break of ≥ 6.0%, or ≥ 6.5%, or ≥ 7.0%, or ≥ 7.5%, or ≥ 8.0%, or ≥ 9.0%. In one embodiment or a combination of two or more embodiments, each of the compositions described herein has a tensile strain at break of ≥ 10%, or ≥ 11%, or ≥ 12%, or ≥ 13%, or ≥ 14%, or ≥ 15%.

[0038] In one embodiment or a combination of two or more embodiments, each of the compositions described herein has a Young's modulus of ≥ 100 MPa, or ≥ 105 MPa, or ≥ 110 MPa, or ≥ 112 MPa, or ≥ 114 MPa, or ≥ 116 MPa, or ≥ 118 MPa, or ≥ 120 MPa. In one embodiment or a combination of two or more embodiments, each of the compositions described herein has a Young's modulus of ≥ 150 MPa, or ≥ 200 MPa, or ≥ 250 MPa, or ≥ 300 MPa.

[0039] An article comprising at least one component formed from any one embodiment or a combination of two or more embodiments described herein is also provided. In one embodiment or a combination of two or more embodiments, the article described herein is a carpet.

[0040] In one embodiment or a combination of two or more embodiments, each of the compositions of the invention described herein is in one or more features such as monomer(s) type and / or amount, Tm, Tc, Tg, density, viscosity (177°C), Mn, Mw, MWD, or any combination thereof, additionally in one or more features such as monomer(s) type and / or amount, Tm, Tc, Tg, density, viscosity (177°C), or a combination thereof Component a It further comprises thermoplastic polymers different from the above. The polymers include, but are not limited to, ethylene-based polymers, propylene-based polymers, and olefin multiblock copolymers. Suitable ethylene-based polymers include, but are not limited to, linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), ultra-low-density polyethylene (ULDPE), homogeneously branched linear ethylene-based polymers, and homogeneously branched substantially linear ethylene-based polymers (i.e., homogeneously branched long-chain branched ethylene polymers). Examples of propylene-based polymers include polypropylene homopolymers and other propylene / ethylene copolymers.

[0041] wax

[0042] Waxes include, but are not limited to, paraffin wax, microcrystalline wax, polyethylene wax, polypropylene wax, Fischer-Tropsch wax, oxidized Fischer-Tropsch wax, hydroxy stearamide wax, adipose amide wax, and combinations thereof. Additional waxes include animal wax, plant wax, and combinations thereof.

[0043] oil

[0044] Oils include, but are not limited to, mineral oils such as naphthenic, paraffinic, or hydrogenated (white) oils; vegetable oils and animal oils and their derivatives; oils derived from petroleum; and combinations thereof. Additional oils include liquid polyolefins such as liquid polybutene; and phthalates such as diisoundecyl phthalate, diisononyl phthalate, and dioctyl phthalate; and combinations thereof.

[0045] Tackifier

[0046] Tackifiers are known in the art and may be solid, semi-solid, or liquid at room temperature. Tackifiers include, but are not limited to, aliphatic hydrocarbon resins (hydrogenated or unhydrogenated), aromatic hydrocarbon resins (hydrogenated or unhydrogenated), hydrogenated polycyclopentadiene resins, polycyclopentadiene resins, gum rosin, gum rosin esters, wood rosin, wood rosin esters, tall oil rosin, tall oil rosin esters, polyterpenes, aromatically modified polyterpenes, terpene phenols, aromatically modified hydrogenated polycyclopentadiene resins, hydrogenated aliphatic resins, hydrogenated aliphatic aromatic resins, hydrogenated terpenes and modified terpenes, hydrogenated rosin acids, hydrogenated rosin esters, derivatives thereof, and combinations thereof. Preferred tackifiers are selected from hydrogenated aliphatic hydrocarbon resins and hydrogenated aromatic hydrocarbon resins.

[0047] additives

[0048] The composition of the present invention may include one or more additives. Non-limiting examples of suitable additives include fillers, antioxidants, flame retardants, and antimicrobial agents. Fillers include, but are not limited to, calcium carbonate (CaCO3), coal fly ash, barium sulfate, and clay (aluminum hydroxide silicate). Fillers may also include high calorific value fillers such as limestone, marble, quartz, silica, and barite (BaSO4).

[0049] In one embodiment, the composition comprises at least one antioxidant. The antioxidant protects the composition from degradation resulting from reaction with oxygen induced by heat, light, or residual catalysts present in commercial materials. Suitable antioxidants include hindered phenols available from BASF, such as IRGANOX 1010, IRGANOX 1076, and IRGANOX 1726. These primary antioxidants, acting as radical scavengers, may be used alone or in combination with other antioxidants, such as phosphite antioxidants available from BASF, such as IRGAFOS 168. In one embodiment, the composition comprises at least one antioxidant in an amount of 0.1 wt%, or 0.2 wt%, or 0.3 to 0.6 wt%, or 0.8 wt%, or 1.0 wt%. The wt% is based on the total weight of the composition.

[0050] definition

[0051] Unless otherwise specified, all parts and percentages are based on weight, except as implied by the context or customary in the art, and all test methods are the most recent as of the filing date of this disclosure.

[0052] As used herein, the term "composition" includes not only the composition but also a mixture of materials including reaction products and decomposition products formed from the material of the composition. Any reaction product or decomposition product is typically present in trace or residual amounts.

[0053] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. Accordingly, the general term polymer includes the terms homopolymer (used to refer to a polymer prepared from only one type of monomer, including the fact that trace impurities may be incorporated into the polymer structure) and copolymer as defined below. Trace impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, the polymer is stabilized by one or more stabilizers, such as one or more antioxidants, in very small amounts ("ppm" amounts).

[0054] As used herein, the term "copolymer" refers to a polymer produced by the polymerization of at least two different types of monomers. Accordingly, the term copolymer includes the term copolymer (used to refer to a polymer produced from two different types of monomers) and a polymer produced from more than two different types of monomers.

[0055] As used herein, the term “olefinic polymer” refers to a polymer that comprises 50% by weight or a majority by weight of an olefin, such as ethylene or propylene, in a polymerized form (based on the weight of the polymer), and may optionally comprise one or more comonomers.

[0056] As used herein, the term "propylene-based polymer" refers to a polymer that comprises a majority weight percent of propylene in a polymerized form (based on the weight of the polymer) and may optionally comprise one or more comonomers.

[0057] As used herein, the term “propylene-based polymer” refers to a polymer that, in a polymerized form (based on the weight of the polymer), contains propylene in most weight percent and may optionally contain at least one comonomer.

[0058] The term “propylene / ethylene copolymer” as used herein refers to a random copolymer comprising propylene monomer and ethylene as the only two monomer types in a polymerized form (based on the weight of the copolymer) in most weight percent.

[0059] The term "propylene / alpha-olefin copolymer" as used herein refers to a random copolymer comprising propylene and alpha-olefin in most weight percent (based on the weight of the copolymer) in a polymerized form.

[0060] The term “propylene / alpha-olefin copolymer” as used herein refers to a random copolymer comprising propylene monomers and alpha-olefins as the only two monomer types in a polymerized form (based on the weight of the copolymer) in most weight percent.

[0061] As used herein, the term “ethylene-based polymer” refers to a polymer that comprises 50% by weight or a majority by weight of ethylene in a polymerized form (based on the weight of the polymer) and may optionally comprise one or more comonomers.

[0062] As used herein, the term "anhydride functionalized and / or carboxylic acid functionalized olefinic polymer" refers to an olefinic polymer comprising an anhydride functional group and / or a carboxylic acid functional group.

[0063] As used herein, the term "anhydride functionalized and / or carboxylic acid functionalized propylene-based polymer" refers to a propylene-based polymer comprising anhydride functional groups and / or carboxylic acid functional groups.

[0064] The terms “comprising,” “including,” “having,” and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether specifically disclosed. To avoid doubt, any composition claimed through the use of the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymers, unless otherwise stated. In contrast, the term “essentially composed” excludes any other components, steps, or procedures from any subsequent enumerated categories, except those that are not essential to the feasibility. The term “composed” excludes any components, steps, or procedures that are not specifically described or listed.

[0065] List of characteristics of some compositions

[0066] A] As a composition, the following ingredient :

[0067] a) A copolymer comprising at least one propylene / ethylene copolymer or at least one propylene / alpha-olefin copolymer, each having the following characteristics:

[0068] i) Melting point Tm (DSC) of 60°C to 85°C,

[0069] ii) Viscosity of 3,000 cP to 30,000 cP (177℃);

[0070] b) At least one wax;

[0071] c) Includes at least one oil;

[0072] Component b for Component c A composition having a weight ratio of 0.30 to 4.0.

[0073] B] In the above A], Component aA composition having Tm ≥ 62°C, or ≥ 63°C, or ≥ 64°C, or ≥ 65°C, or ≥ 66°C, or ≥ 67°C, or ≥ 68°C. Tm is determined from DSC as discussed in the "Test Methods" section.

[0074] C] In the above A] or B], Component a A composition having Tm ≤ 84℃, or ≤ 83℃, or ≤ 82℃, or ≤ 81℃, or ≤ 80℃, or ≤ 79℃, or ≤ 78℃, or ≤ 77℃, or ≤ 76℃.

[0075] D] In any one of the above A] to C] (A] to C], Component a A composition having a viscosity (177°C) ≥ 3,500 cP, or ≥ 4,000 cP, or ≥ 4,200 cP, or ≥ 4,400 cP, or ≥ 4,600 cP, or ≥ 4,800 cP, or ≥ 5,000 cP, or ≥ 5,200 cP, or ≥ 5,400 cP, or ≥ 5,600 cP, or ≥ 5,800 cP, or ≥ 6,000 cP, or ≥ 6,200 cP, or ≥ 6,400 cP, or ≥ 6,600 cP, or ≥ 6,800 cP, or ≥ 7,000 cP, or ≥ 7,200 cP.

[0076] E] In any one of the above A] to D], Component a A composition having a viscosity (177°C) ≤ 28,000 cP, or ≤ 26,000 cP, or ≤ 24,000 cP, or ≤ 22,000 cP, or ≤ 20,000 cP, or ≤ 18,000 cP, or ≤ 16,000 cP, or ≤ 15,000 cP, or ≤ 14,000 cP, or ≤ 13,000 cP, or ≤ 12,000 cP, or ≤ 11,000 cP, or ≤ 10,000 cP.

[0077] F] In any one of A] to E] above, the composition is Component b for Component c A composition having a weight ratio of ≥ 0.35 or ≥ 0.40 or ≥ 0.45 or ≥ 0.50 or ≥ 0.52 or ≥ 0.54 or ≥ 0.56 or ≥ 0.58 or ≥ 0.60 or ≥ 0.62.

[0078] G] In any one of A] to F] above, the composition is Component b for Component c A composition in which the weight ratio of ≤ 3.9, or ≤ 3.8, or ≤ 3.7, or ≤ 3.6, or ≤ 3.5, or ≤ 3.4, or ≤ 3.3, or ≤ 3.2, or ≤ 3.0, or ≤ 2.8, or ≤ 2.6, or ≤ 2.4, or ≤ 2.2, or ≤ 2.0, or ≤ 1.8, or ≤ 1.6.

[0079] H] In any one of the above A] to G], the above Component a A composition having a density / Tm ratio ≥ 0.008, or ≥ 0.009, or ≥ 0.010, or ≥ 0.011. Unit = (g / (cc·℃)).

[0080] I] In any one of the above A] to H], Component a A composition having a density / Tm ratio ≤ 0.020, or ≤ 0.019, or ≤ 0.017, or ≤ 0.016, or ≤ 0.015, or ≤ 0.014. Unit = (g / (cc·℃)).

[0081] J] In any one of the above A] to I], Component a A composition having a density ≥ 0.860 g / cc, or ≥ 0.861 g / cc, or ≥ 0.862 g / cc, or ≥ 0.863 g / cc, or ≥ 0.864 g / cc, or ≥ 0.865 g / cc, or ≥ 0.866 g / cc, or ≥ 0.867 g / cc, or ≥ 0.868 g / cc (1 cc = 1 cm³).

[0082] K] In any one of the above A] to J], Component a A composition having a density ≤ 0.874 g / cc, or ≤ 0.873 g / cc, or ≤ 0.872 g / cc, or ≤ 0.871 g / cc, or ≤ 0.870 g / cc.

[0083] L] In any one of the above A] to K], Component a A composition having a crystallization temperature Tc ≥ 15℃, or ≥ 16℃, or ≥ 17℃, or ≥ 18℃, or ≥ 19℃, or ≥ 20℃.

[0084] M] In any one of the above A] to L], Component a A composition having a crystallization temperature Tc ≤ 40℃, or ≤ 39℃, or ≤ 38℃, or ≤ 37℃, or ≤ 36℃, or ≤ 35℃, or ≤ 34℃, or ≤ 33℃, or ≤ 32℃.

[0085] N] In any one of the above A] to M], Component a A composition having a glass transition temperature Tg ≥ -35℃, or ≥ -34℃, or ≥ -33℃, or ≥ -32℃, or ≥ -31℃.

[0086] O] In any one of the above A] to N], Component a A composition having a glass transition temperature Tg ≤ -25℃, or ≤ -26℃, or ≤ -27℃, or ≤ -28℃, or ≤ -29℃.

[0087] P] In any one of the above A] to O], Component a A composition having a weight average molecular weight Mw ≥ 30,000 g / mol, or ≥ 32,000 g / mol, or ≥ 34,000 g / mol, or ≥ 36,000 g / mol, or ≥ 38,000 g / mol, or ≥ 40,000 g / mol, or ≥ 42,000 g / mol, or ≥ 43,000 g / mol.

[0088] Q] In any one of the above A] to P], Component a A composition having a weight average molecular weight Mw ≤ 60,000 g / mol, or ≤ 58,000 g / mol, or ≤ 56,000 g / mol, or ≤ 54,000 g / mol, or ≤ 52,000 g / mol, or ≤ 50,000 g / mol, or ≤ 48,000 g / mol, or ≤ 47,000 g / mol.

[0089] R] In any one of the above A] to Q], Component a A composition having a number average molecular weight Mn ≥ 10,000 g / mol, or ≥ 12,000 g / mol, or ≥ 14,000 g / mol, or ≥ 16,000 g / mol, or ≥ 18,000 g / mol.

[0090] S] In any one of the above A] to R], Component a A composition having a number average molecular weight Mn ≤ 32,000 g / mol, or ≤ 30,000 g / mol, or ≤ 28,000 g / mol, or ≤ 26,000 g / mol, or ≤ 24,000 g / mol, or ≤ 22,000 g / mol, or ≤ 20,000 g / mol.

[0091] T] In any one of the above A] to S], Component a A composition having a molecular weight distribution MWD(= Mw / Mn) ≥ 1.80, or ≥ 2.00, or ≥ 2.10, or ≥ 2.20, or ≥ 2.30.

[0092] U] In any one of the above A] to T], Component a A composition having a molecular weight distribution MWD ≤ 3.00, or ≤ 2.80, or ≤ 2.70, or ≤ 2.60, or ≤ 2.50, or ≤ 2.40.

[0093] V] In any one of the above A] to U], Component aA composition comprising a propylene / ethylene copolymer, and additionally a propylene / ethylene copolymer.

[0094] W] In any one of the above A] to U], Component a A composition comprising a propylene / alpha-olefin copolymer, and additionally a propylene / alpha-olefin copolymer.

[0095] X] A composition in which, in the above W], the alpha-olefin is a C4-C20 alpha-olefin, additionally a C4-C10 alpha-olefin, and additionally a C4-C8 alpha-olefin.

[0096] Y] A composition comprising, in any one of A] to X] above, a filler comprising ≤ 1.00 wt%, or ≤ 0.50 wt%, or ≤ 0.20 wt%, or ≤ 0.10 wt%, or ≤ 0.05 wt% based on the weight of the composition.

[0097] Z] A composition that does not include a filler in any one of A] to Y] above.

[0098] AA] In any one of A] to Z] above, the composition not containing a filler has a viscosity (165°C) ≥ 800 cP, or ≥ 900 cP, or ≥ 1000 cP, or ≥ 1100 cP, or ≥ 1200 cP.

[0099] BB] In any one of A] to AA] above, the composition not containing a filler has a viscosity (165°C) ≤ 3000 cP, or ≤ 2800 cP, or ≤ 2600 cP, or ≤ 2400 cP, or ≤ 2200 cP, or ≤ 2200 cP, or ≤ 1800 cP, or ≤ 1600 cP, or ≤ 1400 cP.

[0100] CC] In any one of A] to BB] above, the composition not containing a filler is ≥ 34 wt%, or ≥ 36 wt%, or ≥ 38 wt%, or ≥ 40 wt% based on the weight of the composition Component a A composition comprising

[0101] DD] In any one of A] to CC] above, the composition not containing a filler is ≤ 50 wt%, or ≤ 48 wt%, or ≤ 46 wt%, or ≤ 44 wt% based on the weight of the composition Component a A composition comprising

[0102] EE] In any one of A] to DD] above, the composition not containing a filler is ≥ 40 wt%, or ≥ 42 wt%, or ≥ 44 wt%, or ≥ 46 wt%, or ≥ 48 wt%, or ≥ 50 wt%, or ≥ 52 wt% based on the weight of the composition Components a, b, and c A composition comprising the sum of

[0103] FF] In any one of A] to EE] above, the composition not containing a filler is ≤ 70 wt%, or ≤ 68 wt%, or ≤ 66 wt%, or ≤ 64 wt%, or ≤ 62 wt%, or ≤ 60 wt%, or ≤ 58 wt% based on the weight of the composition Components a, b, and c A composition comprising the sum of

[0104] GG] In any one of the above A] to X], Ingredient d) : A composition comprising at least one additional filler.

[0105] HH] In the above GG], the composition is Component d for component a A composition in which the weight ratio of ≥ 5.00, or ≥ 6.00, or ≥ 7.00, or ≥ 8.00.

[0106] II] In the above GG] or HH], the composition is Component d for component aA composition in which the weight ratio of ≤ 15.0, or ≤ 14.0, or ≤ 13.0, or ≤ 12.0, or ≤ 11.0, or ≤ 10.0.

[0107] JJ] In any one of the above GG] to II], the composition comprises ≥ 55.0 wt%, or ≥ 60.0 wt%, or ≥ 65.0 wt%, or ≥ 70.0 wt%, or ≥ 75.0 wt%, or ≥ 77.0 wt% based on the weight of the composition Ingredient d A composition comprising

[0108] KK] In any one of the above GG] to JJ], the composition comprises ≤ 90.0 wt%, or ≤ 88.0 wt%, or ≤ 86.0 wt%, or ≤ 84.0 wt%, or ≤ 82.0 wt%, or ≤ 80.0 wt% based on the weight of the composition Ingredient d A composition comprising

[0109] LL] In any one of the above A] to KK], Ingredient e) : An anhydride functionalized and / or carboxylic acid functionalized olefinic polymer, further comprising an anhydride-grafted and / or carboxylic acid-grafted olefinic polymer.

[0110] In the above LL], MM] Ingredient e A composition comprising an anhydride functionalized and / or carboxylic acid functionalized propylene-based polymer, additionally an anhydride-grafted and / or carboxylic acid-grafted propylene-based polymer.

[0111] NN] In the above LL] or MM], the composition is Component a for component e A composition in which the weight ratio of ≥ 15, or ≥ 16, or ≥ 17, or ≥ 18, or ≥ 19, or ≥ 20.

[0112] OO] In any one of the above LL to NN], the composition is Component a for component eA composition in which the weight ratio of ≤ 30, or ≤ 28, or ≤ 26, or ≤ 25, or ≤ 24, or ≤ 23, or ≤ 22.

[0113] PP] In any one of the above A] to OO], component f) : A composition further comprising at least one tackifier.

[0114] QQ] In the above PP], the composition is Component a for component f A composition having a weight ratio of ≥ 0.80, or ≥ 0.85, or ≥ 0.90, or ≥ 0.95.

[0115] RR] In the above PP] or QQ], the composition is Component a for component f A composition in which the weight ratio of ≤ 1.20, or ≤ 1.15, or ≤ 1.10, or ≤ 1.05, or ≤ 1.00.

[0116] SS] In any one of the above GG] to RR], Ingredient d A composition comprising ≥ 5.0 wt%, or ≥ 6.0 wt%, or ≥ 7.0 wt%, or ≥ 8.0 wt% based on the weight of the composition Component a A composition comprising

[0117] TT] In any one of the above GG] to SS], Ingredient d A composition comprising ≤ 15.0 wt%, or ≤ 14.0 wt%, or ≤ 13.0 wt%, or ≤ 12.0 wt%, or ≤ 11.0 wt%, or ≤ 10.0 wt% based on the weight of the composition Component a A composition comprising

[0118] UU] In any one of the above GG] to TT], Ingredient d A composition comprising ≥ 5.0 wt%, or ≥ 6.0 wt%, or ≥ 7.0 wt%, or ≥ 8.0 wt%, or ≥ 9.0 wt%, or ≥ 10.0 wt% based on the weight of the composition Components a, b, and cA composition comprising the sum of

[0119] VV] In any one of the above GG] to UU], Ingredient d A composition comprising ≤ 20 wt%, or ≤ 18 wt%, or ≤ 16 wt%, or ≤ 14 wt%, or ≤ 12 wt% based on the weight of the composition Components a, b, and c A composition comprising the sum of

[0120] WW] In any one of the above GG] to VV], Ingredient d A composition comprising a viscosity (165°C) ≥ 10,000 cP, or ≥ 12,000 cP, or ≥ 14,000 cP, or ≥ 16,000 cP, or ≥ 18,000 cP, or ≥ 20,000 cP.

[0121] XX] In any one of the above GG] to WW], Ingredient d A composition comprising a viscosity (165°C) ≤ 50,000 cP, or ≤ 48,000 cP, or ≤ 46,000 cP, or ≤ 44,000 cP, or ≤ 42,000 cP, or ≤ 40,000 cP, or ≤ 38,000 cP, or ≤ 36,000 cP, or ≤ 34,000 cP.

[0122] YY] In any one of the above A] to XX], " Ingredient d Regarding the viscosity (165°C) of a composition not containing Ingredient d A composition comprising a viscosity (at 165°C) ratio of ≥ 3.0, or ≥ 5.0, or ≥ 7.0, or ≥ 10.0, or ≥ 12.0, or ≥ 14.0, or ≥ 16.0, or ≥ 18.0, or ≥ 20.0, or ≥ 22.0, or ≥ 24.0.

[0123] ZZ] In any one of the above A] to YY], " Ingredient d Regarding the viscosity (165°C) of a composition not containing Ingredient d A composition comprising a viscosity (at 165°C) ratio of ≤ 65, or ≤ 55, or ≤ 50, or ≤ 48, or ≤ 46, or ≤ 44, or ≤ 42, or ≤ 40, or ≤ 38, or ≤ 36, or ≤ 34, or ≤ 32, or ≤ 30.

[0124] A3] In any one of A] to ZZ] above, the composition is a composition having a fracture tensile strain of ≥ 6.0%, or ≥ 6.5%, or ≥ 7.0%, or ≥ 7.5%, or ≥ 8.0%, or ≥ 9.0%.

[0125] B3] In any one of A] to A3] above, the composition is a composition in which the tensile strain at break is ≥ 10%, or ≥ 11%, or ≥ 12%, or ≥ 13%, or ≥ 14%, or ≥ 15%.

[0126] C3] In any one of A] to B3] above, the composition is a composition having a fracture tensile strain of ≤ 60%, or ≤ 50%, or ≤ 40%.

[0127] D3] In any one of A] to C3] above, the composition is a composition having a Young's modulus of ≥ 100 MPa, or ≥ 105 MPa, or ≥ 110 MPa, or ≥ 112 MPa, or ≥ 114 MPa, or ≥ 116 MPa, or ≥ 118 MPa, or ≥ 120 MPa.

[0128] E3] In any one of A] to D3] above, the composition is a composition having a Young's modulus of ≥ 150 MPa, or ≥ 200 MPa, or ≥ 250 MPa, or ≥ 300 MPa.

[0129] F3] In any one of A] to E3] above, the composition is a composition having a Young's modulus of ≤ 1000 MPa, or ≤ 900 MPa, or ≤ 800 MPa, or ≤ 700 MPa.

[0130] G3] In any one of A] to F3] above, the composition is in one or more features such as monomer(s) type and / or amount, Tm, Tc, Tg, density, viscosity (177°C), Mn, Mw, MWD, or a combination thereof, and additionally in one or more features such as monomer(s) type and / or amount, Tm, Tc, Tg, density, viscosity (177°C), or a combination thereof Component a A composition further comprising a thermoplastic polymer different from

[0131] H3] An article comprising at least one component formed from any one of the compositions A] to G3] above.

[0132] I3] In the above H3], the article is a carpet.

[0133] Test method

[0134] Differential Scanning Calorimetry (DSC)

[0135] Differential Scanning Calorimetry (DSC) is used to measure Tm, Tc, Tg, and degree of crystallinity of propylene-based (PP) and ethylene-based (PE) samples. Each sample (0.5 g) was compression-molded into a film at 25,000 psi and 190°C for 10–15 seconds. Approximately 5 to 8 mg of the film sample was weighed and placed in a DSC pan. The lid of the pan was crimped to ensure sealed pressure. The sample pan was placed in the DSC cell and heated to a temperature of 230°C for PP (180°C for PE) at a rate of approximately 10°C / min. The sample was held at this temperature for 3 minutes. Then, the sample was cooled to -60°C for PP (-90°C for PE) at a rate of 10°C / min and held isothermally at that temperature for 3 minutes. Next, the sample was heated at a rate of 10°C / min until it was completely melted (second heating). Unless otherwise noted, the melting point (Tm) and glass transition temperature (Tg) of each polymer sample were determined from the second heating curve, and the crystallization temperature (Tc) was determined from the first cooling curve. Tg and their respective peak temperatures were recorded for Tm and Tc. The percentage crystallinity can be calculated by dividing the heat of fusion (Hf) determined from the second heating curve by the theoretical heat of fusion of 165 J / g for PP (292 J / g for PE) and multiplying this amount by 100 (e.g., Crystallinity % = (Hf / 165 J / g) x 100 (for PP)).

[0136] Gel Permeation Chromatography (GPC) - Propylene-based Polymer

[0137] A high-temperature gel permeation chromatography (GPC) system equipped with a robotic assistant deliver (RAD) system for sample preparation and sample injection was used. The concentration detector was an infrared detector (IR4) from Polymer Char Inc. (Valencia, Spain). Data acquisition was performed using a Polymer Char DM 100 data acquisition box. This system was equipped with an online solvent degassing device from Agilent. The column compartment was operated at 150°C. The columns were four Mixed A LS 30 cm, 20-micron columns. The solvent was nitrogen (N2)-purged 1,2,4-trichlorobenzene (TCB) containing approximately 200 ppm of 2,6-di-t-butyl-4-methylphenol (BHT). The flow rate was 1.0 mL / min, and the injection volume was 200 μl. A sample concentration of "2 mg / mL" was prepared by dissolving the sample in preheated TCB (containing 200 ppm BHT) that was N2 purged at 160°C for 2.5 hours while gently stirring the sample.

[0138] The GPC column set was calibrated by running 20 narrow molecular weight distribution polystyrene (PS) standards. The molecular weight (MW) range of the standard materials is 580 to 8,400,000 g / mol, and the standard materials are contained in six "cocktail" mixtures. Each standard mixture had at least a 10 interval between individual molecular weights. The equivalent polypropylene molecular weight of each PS standard was calculated using the following equation (1) along with the Mark-Houwink coefficients reported for polypropylene (reference [Th.G. Scholte, NLJ Meijerink, HM Schoffeleers and AMG Brands, J. Appl Polym. Sci., 29, 3763-3782 (1984)]) and polystyrene (reference [EP Otocka, RJ Roe, NY Hellman, PM Muglia, Macromolecules, 4, 507 (1971)]):

[0139]

[0140] Here, M PP is the PP equivalent MW, and PS is the PS equivalent MW. Mark-Huink coefficients for PP and PS log K and a The values ​​are listed in Table A below.

[0141] [Table A]

[0142]

[0143] Logarithmic molecular weight corrections were generated using a fourth-order polynomial fitting as a function of elution volume. Number-average and weight-average molecular weights were calculated according to the following formula:

[0144] (2), (3),

[0145] Here w fi and M i are the weight fraction and molecular weight of elution component i, respectively (Note: MWD = Mw / Mn).

[0146] Melting index

[0147] The melt flow rate (MFR) of propylene-based polymers is measured according to ASTM D-1238, conditions 230°C / 2.16 kg. The melt index (I2) of ethylene-based polymers is measured according to ASTM D-1238, conditions 190°C / 2.16 kg.

[0148] density

[0149] ASTM D4703 was used to prepare polymer plaques for density analysis. The density of each polymer was measured using ASTM D792, Method B.

[0150] Viscosity of the unfilled composition

[0151] ASTM D1986 Standard Test for Apparent Viscosity of Hot Melt Adhesives and Coating Materials Viscosity was measured at 165°C on a spindle SC4-31 using a Brookfield viscometer with a Thermosel, Model LVDV-1 Prime, in accordance with the above. The sample was added to the sample chamber, then inserted into the Brookfield Thermosel and secured in place. The sample chamber had a notch on the bottom that fit the bottom of the Brookfield Thermosel to prevent the chamber from rotating when the spindle was inserted and spinning. The sample (approx. 8-10 g) was heated to the required temperature until the molten sample was about 1 inch below the top of the sample chamber. The viscometer unit was lowered and the spindle was immersed in the sample chamber. The viscometer was continued to be lowered until the bracket of the viscometer was aligned with the Thermosel. The viscometer was turned on and set to operate at a shear rate, taking torque readings ranging from 40% to 60% of the total torque capacity based on the viscometer's RPM output. Readings were taken every minute for 30 minutes or until the value stabilized, at which point the final reading was recorded.

[0152] Viscosity of the filler composition

[0153] The viscosity of each charge composition was measured using a Brookfield viscometer, model DV2THBTJ0 Prime, equipped with a Thermosel at 165°C using the SC4-29 spindle. A sample (approx. 22 g) was weighed and added to a sample vial. The sample vial was placed in the Thermosel and melted. Next, the SC4-29 spindle was placed on the sample. Using the RHEOCALC T software or the instrument's "Manual Mode," the spindle was rotated at 3 RPM for 10 minutes. Immediately thereafter, the speed was increased to 40 RPM, and data was collected every minute for 30 minutes. Viscosity was reported as the average of the last five readings (the last five minutes).

[0154] Polymer viscosity

[0155] The viscosity (8-10 g) of each polymer was measured according to ASTM D3236 using a Brookfield viscometer, Model LVDV-1 Prime, equipped with a Thermosel. Viscosity was measured at 177°C using a spindle SC4-31.

[0156] Compression molding

[0157] Each composition was compression molded using a Carver press to produce one or more plates for physical testing. The plaque dimensions were "6 inches x 2.5 inches x 0.08 inches thick". The polymer was pre-melted at 5,000 lb for 1 minute at 190°C, then compressed at 30,000 lb for 5 minutes, and then cooled between cooling plates at 17°C for 1 minute.

[0158] Micro-tensile test - Mechanical properties

[0159] Microtensile data for each compression-molded plaque (see above) were collected in an INSTRON 5565 equipped with a 100 N load cell. Each plaque was die-cut using a NAEF punch press with an "ASTM Die D1708" to form microtensile rods 0.08 inches thick. A strain of 0.100 inches / min was applied to each tensile rod until fracture (fracture was defined as load < 0.25 N). A minimum of three and a maximum of five samples were taken for each composition, and the average value of each characteristic was reported.

[0160] experiment

[0161] commercial materials

[0162] Commercial materials are listed in Table 1 below.

[0163] [Table 1]

[0164]

[0165] Polymer Synthesis and Properties

[0166] Each propylene-ethylene copolymer was produced using a solution polymerization process in a single-liquid complete reactor configuration. Solvent (ISOPAR E) pressure was delivered using industry-standard positive displacement pump technology. The ISOPAR E flow was metered to maintain the solvent for the polymer production ratios listed in Table 2 below. Propylene pressure was also delivered using standard positive displacement pump technology. Propylene was metered to maintain the solvent-to-propylene ratios listed in Table 2. Propylene was combined with the solvent downstream of the solvent flow meter. Ethylene pressure was delivered using industry-standard gas compressor technology. The ethylene flow was metered to maintain the propylene-to-ethylene ratios listed in Table 2. Hydrogen supply pressure was delivered from a gas cylinder. The hydrogen flow was metered to maintain the hydrogen-to-polymer production ratios recorded in Table 2. Hydrogen was combined with the ethylene gas downstream of the ethylene flow meter. The combined gas streams were mixed with the combined liquid streams. Solvent, propylene, and ethylene flows were measured using standard Coriolis meters, and the hydrogen flow was measured using standard thermal mass flow meters. Polymer viscosity was controlled by adjusting the hydrogen-to-polymer production ratio. To reduce polymer viscosity, the hydrogen-to-polymer ratio was increased, which generated more hydrogen flow into the reactor. To increase polymer viscosity, the hydrogen-to-polymer ratio was decreased, which reduced hydrogen flow into the reactor.

[0167] The combined feed stream was routed through a heat exchanger system to cool the stream to the target feed temperature listed in Table 2. The flow from the heat exchanger system was directed to the reactor, where it was injected into the polymerization solution. The feed pressure was not directly controlled. The control point was the reactor pressure. Therefore, the feed pressure was the result of the pressure drop in the feed system relative to the given total flow rate.

[0168] The pressure required to inject each catalyst component into the reactor was delivered using industry-standard positive displacement pump technology. Flow rates were measured using a Coriolis meter. Each component was pumped and metered individually. The catalyst complex was injected into the reactor separately from the co-catalyst. Co-catalyst 2 was combined with co-catalyst 1, and the combined stream was injected into the reactor. As a result of this configuration, the catalyst complex was activated in the reactor.

[0169] The propylene conversion rate was controlled at the values ​​listed in Table 2 by adjusting the flow of the catalyst complex. The flow of co-catalyst 1 and co-catalyst 2 was adjusted to maintain a constant molar ratio of each component to the catalyst. The ethylene conversion rate was controlled by the relative reactivity of propylene to ethylene with respect to the selected catalyst complex and the propylene conversion set point.

[0170] Copolymers were produced using two different catalyst complexes of the bis-biphenylphenoxy series. HIPO 1 and HIPO 4 were prepared using catalyst A, while HIPO 2 and HIPO 3 were prepared using catalyst B. The procedures for synthesizing catalysts A and B, respectively, can be found in WO 2012 / 027448 and WO 2007 / 136493. Both catalysts contain a hafnium metal center (M), and their structures are shown in Table 3 below. Each catalyst was activated by contacting the metal-ligand complex with bis(hydrogenated tallow alkyl)methyl tetrakis(pentafluorophenyl)borate (1<->) amine (co-catalyst 1) and MMAO (co-catalyst 2). Refer to Table 3.

[0171] The exothermic heat of polymerization was removed through the adiabatic temperature rise of the solvent and reactants from the feed to the reactor temperature and the non-adiabatic heat removal through heat exchange to maintain the reactor temperature in Table 2. The polymerization reaction was terminated by injecting water into the reactor effluent. The polymer was separated in the form of a veal. The polymer can be stabilized with one or more antioxidants at a concentration of 1000–1500 ppm. The polymer properties are shown in Tables 4A and 4B.

[0172] [Table 2]

[0173]

[0174] [Table 3]

[0175]

[0176] [Table 4A]

[0177]

[0178] [Table 4B]

[0179]

[0180] Research - Filling Composition

[0181] Composition - Blending with fillers

[0182] The compositions are presented in Table 5. The mixing of each filled composition was performed in a HAAKE RHEOMIX 3000 rotating at 8 RPM. The polymer (HIPO or commercial polymer) and the functionalized copolymer (MORTON 100P) were added to the mixer at 140°C and mixed until melted. The filler (CaCO3) was divided into three portions. The first portion of the filler was added to the mixer and mixed for a short time. Then, the second portion of the filler was added to the mixer and the ram was lowered. The RPM was increased to 60 RPM and mixing was continued for 1 minute, after which the RPM was decreased to 15 RPM and mixing was continued for 1 minute. The final portions of the filler, wax, and IRGANOX 1010 were added, the ram was lowered, and the resulting mixture was mixed at 60 RPM for 10 minutes. Next, the tackifier and oil were added, the ram was lowered, and the resulting mixture was mixed for 2 minutes, then the RPM was reduced to 15 RPM and mixing was continued for 1 minute. The mixture collected in the ram was scraped back into the bowl, the RPM was increased to 60 RPM, and mixing was continued for 2 minutes. The RPM was increased to 90 RPM and mixing was continued for 3 minutes. The final mixture was collected in a HAAKE RHEOMIX and flattened for future tests (compression molding and microtensile testing).

[0183] Each composition in Table 5 was compression molded (see "Test Methods" section) and its mechanical properties were investigated by micro-tensile testing. The mechanical properties are shown in Table 6.

[0184] [Table 5]

[0185]

[0186] As can be seen in Table 6, compositions 1-4 of the present invention exhibit an optimal combination of high Young's modulus and high tensile strain at break. The compositions of the present invention exhibit improved flexibility, as can be seen from the higher tensile strain at break (%) values. In addition, Young's modulus is a good indicator of the thermal stability and expansion strength of the compositions. Compositions 1 and 4 of the present invention have the best combination of sufficiently high modulus values ​​(less than 450 MPa and greater than 60 MPa) and high tensile strain at break values, and this combination allows for reduced buckling of the carpet backsheet during the carpet's service life, in addition to improved flexibility of the carpet backsheet.

[0187] The unfilled viscosity of all compositions except Comparative Composition A is significantly lower than the manufacturing requirement of an unfilled viscosity (165°C) of 30,000 cP or less. It is noted that Comparative Composition A is formed from the high-viscosity copolymer VERSIFY 4200. Furthermore, each composition of the present invention, being a filled thermoplastic material, can be re-extruded multiple times with almost no loss of mechanical performance. This can be accomplished using various conversion techniques, including the most commonly used methods of single-screw or double-screw extrusion. This also allows these formulations to be recycled in carpet applications or other applications where the high-filled formulations provide the necessary performance characteristics.

[0188] [Table 6]

[0189]

Claims

Claim 1 As a composition, the following ingredient : a) At least one propylene / ethylene copolymer or at least one propylene / alpha-olefin copolymer, each comprising the following properties: i) a melting point Tm of 60°C to 85°C, ii) a viscosity of 3,000 cP to 30,000 cP (177°C); b) At least one wax; c) At least one oil - here, Component b for Component c Having a weight ratio of 0.30 to 4.0; and d) At least one filler - here, Component a for Ingredient d A composition comprising having a weight ratio of 5.00 or more. Claim 2 In paragraph 1, the above Component a A composition having a density of ≥ 0.860 g / cc. Claim 3 In paragraph 1 or 2, the above Component a A composition having a density of ≤ 0.874 g / cc. Claim 4 In paragraph 1 or 2, the above Component a A composition that is a propylene / ethylene copolymer. Claim 5 In paragraph 1 or 2, the above Component a A composition that is a propylene / ethylene copolymer. Claim 6 In paragraph 1 or 2, Component a for Ingredient d A composition having a weight ratio of 15.0 or less. Claim 7 In paragraph 1 or 2, component f) : A composition further comprising at least one tackifier. Claim 8 In paragraph 6, the above Ingredient d A composition having a viscosity (at 165°C) of ≤ 50,000 cP. Claim 9 A composition according to claim 1 or 2, wherein the fracture tensile strain is ≥ 6.0%. Claim 10 An article comprising at least one component formed from the composition of claim 1 or 2. Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete

Citation Information

Patent Citations

  • Adhesive compositions comprising low molecular weight functionalized olefin-based polymers

    KR1020170043547A

  • Compositions containing low molecular weight propylene-based polymers

    KR1020180034474A

  • Carpet backing layer composition

    KR1020200030072A

  • Polypropylene-based adhesive composition

    JP2013540867A